Characteristics of ultra-fine bubble water and its trials on enhanced methane production from waste activated sludge. (February 2019) - Wang, Di; Yang, Xiaojing; Tian, Caixing; Lei, Zhongfang; Kobayashi, Noriko; Kobayashi, Motoyoshi; Adachi, Yasuhisa; Shimizu, Kazuya; Zhang, Zhenya
Graphical abstract: Highlights: Hundreds of millions of nanoscale bubbles can exist stably in water for >14 days. The negative zeta potential of UFBs is affected by solution pH and the gas introduced. Addition of UFBW to AD system can effectively enhance methane production. Air-UFBW was also found to have enhancement effect on anaerobic fermentation. Both nanoscale UFBs and the introduced gas play important roles in the AD process. Abstract: In this study biogas production efficiency was evaluated by adding ultra-fine bubble water (UFBW) into waste activated sludge (WAS) through anaerobic digestion (AD). Four kinds of gases, i.e. Air, N2, CO2 and H2 were introduced into tap water (TW) to prepare the UFBW with their properties being first investigated. Results show that hundreds of millions of nanoscale bubbles with the negative zeta potential could be stable in the UFBW for longer than two weeks whereas almost no nanometer bubbles could be detected in the raw TW. As for their impact on subsequent AD of WAS, the cumulative methane production with the addition of UFBW was 14–21% higher than that from the raw TW addition group. Interestingly, the Air-UFBW also could promote the biogas production in this study, which is different from the common understanding of AD, an obligate anaerobic process.